Pengaruh Kompetensi Aparatur Desa Dan Gaya Kepemimpinan Terhadap Kualitas Laporan Keuangan Desa - Tri Ayu Yulianti Kotta; Rusman Soleman; Irfan Zamzam (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Village governments need to apply the principles of transparency and accountability in order to produce quality accounting information, villages must also manage their finances which come from natural resources which have a large role accepted by the village government. This research aims to find out how the competence of village officials and leadership style influence the quality of village financial reports. This research uses descriptive research. The data collection technique in this research is by conducting a field survey, namely using a questionnaire. The results of this research indicate that there is a significant positive influence of the village apparatus competency and leadership style variables on the quality of financial reports